Race disparities in mortality by breast cancer from 2000 to 2017 in São Paulo, Brazil: a population-based retrospective study - Ana Cláudia Marcelino; Bruno Gozzi; Cássio Cardoso-Filho; Helymar Machado; Luiz Carlos Zeferino; Diama Bhadra Vale (BMC Cancer, 2021)
Abstract Background In Brazil, inequalities in access may interfere with cancer care. This study aimed to evaluate the influence of race on breast cancer mortality in the state of São Paulo, from 2000 to 2017, contextualizing with other causes of death. Methods A population-based retrospective study using mortality rates, age and race as variables. Information on deaths was collected from the Ministry of Health Information System. Only white and black categories were used. Mortality rates were age-adjusted by the standard method. For statistical analysis, linear regression was carried out. Results There were 60,940 deaths registered as breast cancer deaths, 46,365 in white and 10,588 in black women. The mortality rates for 100,000 women in 2017 were 16.46 in white and 9.57 in black women, a trend to reduction in white (p = 0.002), and to increase in black women (p = 0.010). This effect was more significant for white women (p < 0.001). The trend to reduction was consistent in all age groups in white women, and the trend to increase was observed only in the 40–49 years group in black women. For ‘all-cancer causes’, the trend was to a reduction in white (p = 0.031) and to increase in black women (p < 0.001). For ‘ill-defined causes’ and ‘external causes’, the trend was to reduce both races (p < 0.001). Conclusion The declared race influenced mortality rates due to breast cancer in São Paulo. The divergences observed between white and black women also were evident in all cancer causes of death, which may indicate inequities in access to highly complex health care in our setting.